What is America Eating? : Proceedings of a Symposium (National Academy Press, 1986)
Explaining dietary habits, this volume examines the impact of fast-food proliferation and the changing role of women as it affects dietary behavior, and analyzes the nutritional consequences of national dietary trends. It focuses on the factors that shape eating patterns, eating trends such as snacking and food variety, nutrition policy, and more.